Lateral–torsional buckling of cold-formed channel sections subject to combined compression and bending - Cheng, Shan-shan; Kim, Boksun; Li, Long-yuan (Journal of constructional steel research, 2013)
This paper presents an analytical study of the flexural buckling and lateral–torsional buckling of cold-formed steel channel section beams subject to combined compression and bending about their major and minor axes. For channel section beams a bending about the minor axis creates a non-symmetric pre-buckling stress distribution, which has a significant influence on the lateral–torsional buckling of the beams. This kind of feature has not been discussed in the existing literature. The focus of this present study is the interaction between the compression load and the bending moments about the major and minor axes. It has been found that for a section subject to combined compression and the major-axis bending the bending moment will decrease the critical compression load, although the critical value of the largest compressive stress in the section actually increases with the applied bending moment. However, for a section subject to combined compression and the minor-axis bending the effect of the bending moment on the critical compression load depends on the direction of bending applied. For bending that creates a compressive stress in the lips the bending moment will reduce the critical compression load. However, for bending that creates a compressive stress in the web the bending moment has almost no influence on the critical compression load. ► It presents an analytical solution for lateral-torsional buckling of CFSS. ► It examines interactions between compression and bending when channel beams buckle. ► It highlights difference in buckling between symmetric and non-symmetric beams. ► Stress variation effect on lateral-torsional buckling of channel beams is emphasized.